1996
DOI: 10.1128/jb.178.21.6110-6115.1996
|View full text |Cite
|
Sign up to set email alerts
|

Direct quantitation of the number of individual penicillin-binding proteins per cell in Escherichia coli

Abstract: The penicillin-binding proteins (PBPs) are a set of enzymes responsible for the terminal stages of peptidoglycan biosynthesis, where they carry out transpeptidation, transglycosylation, endopeptidase, or carboxypeptidase functions. It is the transpeptidation, endopeptidase, and carboxypeptidase functions that are inhibited when these proteins are acylated by a ␤-lactam antibiotic (10). In all cases where this reaction has been investigated biochemically, the ␤-lactam ring opens and forms a covalent bond with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 25 publications
(46 reference statements)
7
92
0
Order By: Relevance
“…Transient interactions between MreB and PBP2 may explain how E. coli maintains robust cell growth despite only expressing ∼100 PBP2 molecules per cell (21). If PBP2 were part of a stable multienzyme complex, then previous calculations have indicated that ∼100 PBP2 molecules would be required to maintain a 20-min doubling time (3), and reductions in PBP2 levels would lead to a decrease in growth rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transient interactions between MreB and PBP2 may explain how E. coli maintains robust cell growth despite only expressing ∼100 PBP2 molecules per cell (21). If PBP2 were part of a stable multienzyme complex, then previous calculations have indicated that ∼100 PBP2 molecules would be required to maintain a 20-min doubling time (3), and reductions in PBP2 levels would lead to a decrease in growth rate.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, transient associations are beneficial for buffering growth against fluctuations in enzyme abundance. At a PBP2 abundance of ∼100 enzymes per cell (21), one would expect 1/√N ∼ 10% fluctuations, yet growth rate remains consistent through cell division (24). In addition, transient association loosens the requirement for an MreB complex to spatially and temporally order the steps of cell wall synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there are only about 100 molecules of FtsI per cell (Spratt, 1977;Dougherty et al, 1996), we used immunofluorescence microscopy (IFM) rather than immunoelectron microscopy (IEM) to visualize FtsI. IFM is more sensitive than IEM, in part because in IFM one views whole cells and can, in principle, detect all of the molecules of a given protein within a cell.…”
Section: Introductionmentioning
confidence: 99%
“…In E. coli the DD-endopeptidase activity appears to be due to redundant catalytic activities of DacB and PbpG, while DD-carboxypeptidase activity appears to be due to the redundant catalytic activities of E. coli DacA, DacC and DacD. In E. coli PbpG has been shown to constitute up to 30% of the total penicillin-binding proteins (Dougherty et al, 1996).…”
Section: The Low-molecular-mass Pbp Familymentioning
confidence: 99%